(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper describes 3-D finite element dynamic analysis of retaining wall structures with consideration of the soil-structure interaction. Purpose of this study is to reduce damages due to earthquake in such structures. For this reason, finite element program ANSYS has been used. The analysis data is based on 1995 Kobe earthquake report and the results have been verified with some retaining walls were damaged in that earthquake. To take into account the non-linearity of soil-structure surface, surface to surface contact element is used. One of the most important problems in dynamic analysis is modeling of infinite media. If hinge or sliding support for soil boundary is used in finite element method, it would not define an acceptable boundary condition, because the transmitted earthquake waves reflect from the boundary and no energy would transmit out. For simulation of the unbounded nature of the soil medium, viscous (dashpot) boundary has been applied. Damping coefficient in both normal and perpendicular directions is given by Lysmer and Kuhlemeyer, and Drucker-Prager soil plasticity model is considered for non-linearity of soil.